2012
DOI: 10.3390/ijms131114262
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Activities of Three Polysaccharide Fractions from Pine Cones

Abstract: The traditional method of gas chromatography-mass spectrometry for monosaccharide component analysis with pretreatment of acetylation is described with slight modifications and verified in detail in this paper. It was then successfully applied to the quantitative analysis of component monosaccharides in polysaccharides extracted from the pine cones. The results demonstrated that the three pine cone polysaccharides all consisted of ribose, rhamnose, arabinose, xylose, mannose, glucose and galactose in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…The antioxidant reacts with ABTS + to cause the reaction to fade and initiate a change in the absorbance of a particular wavelength segment to determine the size of the antioxidant to remove ABTS free radicals [22]. The ABTS radical scavenging activity of polysaccharides was performed according to [23] with slight modification. 7 mmol/L ABTS solution was mixed with 2.45 mmol/L potassium persulfate aqueous solution, and then the mixture was incubated in the dark at room temperature for 12-16 h. Then 3 mL ABTS + solution was added to 1 mL polysaccharide solutions of various concentrations in a test tube.…”
Section: Measurement Of Molecular Weights Of Polysaccharidesmentioning
confidence: 99%
“…The antioxidant reacts with ABTS + to cause the reaction to fade and initiate a change in the absorbance of a particular wavelength segment to determine the size of the antioxidant to remove ABTS free radicals [22]. The ABTS radical scavenging activity of polysaccharides was performed according to [23] with slight modification. 7 mmol/L ABTS solution was mixed with 2.45 mmol/L potassium persulfate aqueous solution, and then the mixture was incubated in the dark at room temperature for 12-16 h. Then 3 mL ABTS + solution was added to 1 mL polysaccharide solutions of various concentrations in a test tube.…”
Section: Measurement Of Molecular Weights Of Polysaccharidesmentioning
confidence: 99%
“…Hemicellulose hydrolysis and monosaccharide derivatization processes were carried out as described by [23]. Galactose, glucose, mannose and xylose contents were determined using gas chromatography with mass spectrometry detection (GCMS-QP2010, Shimadzu, Tokyo, Japan).…”
Section: Analysis Of Monosaccharide Compositionmentioning
confidence: 99%
“…It's clearly shown that the ultrasound treatment samples (ZLP 30 , ZLP 60 , ZLP 90 and ZLP 120 ) have the same functional groups as the native polysaccharide (ZLP 0 ). In fact, The five samples displayed a broad stretching intense characteristic peak at around 3300 cm −1 which was ascribe to the stretching vibration of hydroxyl group (-OH) attributed to inter and intra molecular interaction of the polysaccharides chains [47]. Besides, there is no change in the absorption bands detected at 1605 cm −1 and 1716 cm −1 which are characteristic of the stretching vibration of C = O which attributed respectively to the carboxylate ion (COO-), and the O-acetyl groups [48,49].…”
Section: Chemical Analysismentioning
confidence: 98%